Stability and Hopf Bifurcation of an n-Neuron Cohen-Grossberg Neural Network with Time Delays - Qiming Liu; Sumin Yang (Journal of Applied Mathematics)
A Cohen-Grossberg neural network with discrete delays is investigated in this paper. Sufficient conditions for the existence of local Hopf bifurcation are obtained by analyzing the distribution of roots of characteristic equation. Moreover, the direction and stability of Hopf bifurcation are obtained by applying the normal form theory and the center manifold theorem. Numerical simulations are given to illustrate the obtained results.